(untitled) (GEOMATE Journal, 2022)
In recent years, the damage to bridge foundations caused by heavy rainfall and scouring has increased. In some cases, the entire bridge is carried away, whereas, in others, damage mainly occurs in the foundation, such as settlement and inclination. In the latter cases, it is expected that the damaged bridge is shortly reused after minor repairs are performed only on the superstructure while retaining the residual displacement of the foundation. However, it is difficult to predict whether a foundation with residual displacement possesses the bearing capacity needed to resume emergency use of the damaged bridge. This study focuses on the residual bearing capacity of a shallow foundation after scouring. We performed vertical loading tests on scoured shallow foundations on an aluminum rod ground model to clarify the mechanism. The scouring of the ground was simulated by manually pulling out the aluminum rods. The residual displacement induced by the dead load was measured, and the loading was continued until the residual bearing capacity became clear. We systematically evaluated the effects of scouring volume and shape on the behavior of the foundation. It was found that the residual displacement increased with scouring, but the residual bearing capacity did not necessarily decrease. These findings suggest the possibility of expanding the conditions for the early resumption of damaged foundations and will be helpful for future emergency disaster operations of damaged river bridges.